Partograph utilization is associated with educational status of obstetrics care givers in Ilu Aba Bor Zone, Ethiopia: a cross-sectional study - Aynalem, Getamesay; Teshome , Fentaneh; Negera, Ebissa (Ethiopian Journal of Reproductive Health, 2024)
Background: Worldwide, several thousands of mothers die every year due to pregnancy and birth related complications. Most of maternal deaths can be minimized by using partograph routinely. However, the level of utilization and associated factors among obstetrics care providers in Ilu Aba Bor Zone has been barely known. Objective: This study assessed the level of partograph utilization and its predictors among obstetric care givers working in public health institutions of Ilu Aba Bor Zone, South West Ethiopia. Methods: An institution-based cross-sectional study design was employed. A structured self-administered and pretested questionnaire adapted from available literatures were used. In addition to descriptive statistics, logistic regression analysis was applied to assess association. Results: The level of partograph utilization among obstetrics care providers in the study area was 32.8%. Receiving on-job training on partograph (AOR (Adjusted Odds Ratio) = 2.21, 95%CI (Confidence Interval) = 1.19, 4.11), working in a hospital compared to working in a health center (AOR = 2.43, 95%CI = 1.01, 5.82), having BSc (Bachelor of Science) and above educational status in contrast to having Diploma (AOR = 3.12, 95%CI = 1.59, 6.12), and having partograph in a health facility (AOR= 4.19, 95%CI = 2.12, 8.29) were positively associated with partograph use. Conclusions: Partograph utilization level was much lower than World Health Organization recommendation. On-job training on partograph, work place, educational status, and partograph availability were predictors of level of partograph utilization among the obstetric care givers.